Solutions manual to accompany loss models from data to decisions - Klugman Stuart A; Panjer Harry H; Willmot Gordon E (New Jersey John Wiley, 2008)
Beginning with a framework for model building and a description of frequency and severity loss data typically available, it shows readers how to combine frequency, severity, and loss models to build aggregate loss models and credibility-based pricing mod
Keywords: Insurance-mathematical models; Insurance-statistical methods